Modifiable lifestyle factors are associated with lower pain levels in adults with knee osteoarthritis - A Erin Connelly; Amy J Tucker; Laima S Kott; Amanda J Wright; Alison M Duncan (Pain Research and Management)
BACKGROUND: With no cure or effective treatments for osteoarthritis (OA), the need to identify modifiable factors to decrease pain and increase physical function is well recognized.